Hasil Belajar Konsep Pereaksi Pembatas Berbantuan LKS-Induktif Pada Siswa Kelas X SMA Negeri 1 Palangka Raya Tahun Pelajaran 2018/2019 - Ike Valentie; Abdul Hadjranul Fatah (Jurnal Ilmiah Kanderang Tingang, 2020)
Stoichiometry discuss several concepts, one of which is a limiting reagent. Students studying boundary reagent material need to understand and master the prerequisite concepts namely chemical formulas, chemical equations and mole concepts. The root cause of the low reasoning ability of the concept can be sourced from the teacher, students and the environment. Based on a number of things it requires an appropriate learning strategy where the teacher does not present material that is abstract but guides students thinking in reasoning to obtain new knowledge. One of them is by using Worksheets. Learning that uses worksheet-inductive to be able to optimally increase student learning activities and at the same time motivate students to think critically. Learning using worksheet-inductive affects the ability of students to understand the concept of limiting reagents. This study aims to: describe the learning outcomes of the concept of limiting reagents. This study involved 68 students of class X MIPA-5 and X MIPA-7 Public Senior High School 1 Palangka Raya. The instruments used were the pretest and posttest question sheets, the answer sheets for the practice questions on the worksheet-Inductive. Data was collected through three stages, namely pretest, implementation of worksheet-Inductive learning, and posttest. The data obtained were analyzed descriptively. The results showed that students were able to: (a) apply the precondition concept of 88%; (b) understand the definition of a limiting reagent of 78.2%; and (c) determine the limiting reagent which is converted from the mass, volume, or number of particles of known substances by 71.87%.